Sustainable Low‐Pressure Reverse Osmosis Concentrate Management: Eight Years and Counting. Issue 11 (1st November 2016) - Hobbs, Colin; Arevalo, Jorge; Prah, David; Noble, John; Ponitz, David; Butler, Sam
Abstract : A sustainable method for concentrate management is helping the City of Ormond Beach, Fla., successfully transform an undesirable by‐product into a valuable resource.